Synthesis and Characterization of Ag Nanoparticles for Orthopaedic applications. (2017) - Perli, M.D.; Karagkiozaki, V.; Pappa, F.; Moutsios, I.; Tzounis, L.; Zachariadis, A.; Gravalidis, C.; Laskarakis, A.; Logothetidis, S.
Abstract: Bacterial infections are a leading cause of death for millions of people worldwide, while few antibiotics have been proved effective against multidrug-resistant bacteria. Recently, nanoparticles have been used for the delivery of therapeutic agents to reduce bacterial infections due to their antimicrobial activity and unique mode of action. In our studies, silver nanoparticles (Ag NPs) have been used in order to meddle with associated infections for orthopaedic applications, due to their unique morphology and size. Nanoprecipitation method was used for the development of the NPs, using PVP (polyvinylpyrrolidone) as a reducing agent. Chitosan was used as a stabilizing and a coating agent at different concentrations (0.1%, 0.01% and 0.001%) in order to evaluate the most optimum capped coating. Atomic Force Microscopy (AFM) was the appropriate indicator for the morphological and topography analysis. Results showed that chitosan-capped NPs with 0.01% were found to be the most optimum. Transmittance measurements at plasmon emission at ∼320nm wavelength have showed Ag nanoparticles which were identified due to the sharp absorption peak. Variations of the absolute transmittance values due to the different thickness of the samples confirmed the coating of chitosan in Ag NPs. XRD measurements further took place and successfully have indicated the presence of chitosan in Ag nanoparticles' surface. Electrospinning System was used for the formation of PCL (poly-ε-caprolactone) scaffolds where Ag NPs were deposited via Electrospraying System. The final scaffolds were then studied with AFM and SEM (Scanning Electron Microscopy) Images. As a conclusion, the fabricated Ag NPs into polymer scaffolds appeared to be a valuable tool with antibacterial properties towards implant-associated orthopedic infections.